Orphine usage in the management of pain by doctors in pholosong hospital, Gauteng, South Africa - Nzale, Nzali Arnold (Division of Emergency Medicine, 2026)
Introduction: The World Health Assembly reiterated the ethical duty of healthcare professionals to alleviate pain and suffering. However, in many countries, the appropriate use of opioids for the relief of pain and suffering remained insufficient. Also, the World Health Organisation demonstrated insufficient skills regarding pain management among health care workers and reaffirmed that morphine use was capable of relieving pain in more than ninety percent (90%) of cancer patients when used correctly. Aim: to explore morphine usage by doctors for pain management in Pholosong Regional Hospital in Ekurhuleni, Gauteng Province, South Africa. Objectives: To identify doctors' perceptions of morphine usage, identify factors associated with morphine use, and provide recommendations for the rational use of morphine in health care. Methodology: The study was a descriptive cross-sectional study conducted through a survey of doctors at Pholosong Hospital. Results: For most doctors, eighty-three percent (83%) completed the questionnaires in full. Seventy-two percent (72%) did not prescribe morphine to their patients. The older doctors tended to prescribe morphine less and were less skilled in morphine use. Nearly seventy percent (70%) did not fear the side effects of morphine in their patients. Availability of morphine was reported by fifty percent (50%) and half had received training in morphine prescribing. Conclusions: Significant findings were that most doctors in the hospital had inadequate knowledge and were not skilled enough in morphine use for pain control in their patients. The finding was of concern because pain control was sub- standard in a significant proportion of adult patients managed in the hospital. It is a concern that patients' human rights of freedom from pain and dignity may be breached due to doctors' perceptions of morphine usage. Recommendations include the urgent need to remedy the situation through team-based robust health promotion, doctors' in-service training, clinical guidelines, pain control tools, and making morphine accessible to all parts of the hospital.